2017
DOI: 10.1007/s00380-017-1036-x
|View full text |Cite|
|
Sign up to set email alerts
|

Association between discordance of LDL-C and non-HDL-C and clinical outcomes in patients with stent implantation: from the FU-Registry

Abstract: It is not yet clear whether the discordance of low-density lipoprotein cholesterol (LDL-C) and non-high-density lipoprotein cholesterol (non-HDL-C) predicts the follow-up clinical outcome (major adverse cardiovascular events: MACEs) in patients with coronary stent implantation. Among 2015 patients with coronary stent implantation (Fukuoka University [FU]-Registry), excluding those with acute coronary syndrome or hemodialysis, we selected 801 patients who had undergone successful stent implantation with a follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
2
8
0
1
Order By: Relevance
“…In our study, high level of non-HDL-c/TC, but not non-HDL-c, showed poor outcomes in 1-year follow-up. Our findings are similar to previously published studies [25, 26]. In those studies, statin might be one of the major confounding factors which could affect the non-HDL-c level.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, high level of non-HDL-c/TC, but not non-HDL-c, showed poor outcomes in 1-year follow-up. Our findings are similar to previously published studies [25, 26]. In those studies, statin might be one of the major confounding factors which could affect the non-HDL-c level.…”
Section: Discussionsupporting
confidence: 92%
“…This TZD also significantly increased triglyceride levels in 50 patients who were given at 4 mg/day for 3 months in addition to their usual treatment compared to baseline levels [86,87]. Higher LDL-C level was consistently and independently associated with higher incidences of major adverse cardiovascular events after controlling for conventional risk factors [88]. Third, overload of intravascular volume.…”
Section: Tzds Increase Risks Of Myocardial Infarctionmentioning
confidence: 82%
“…Повышенный уровень ХС ЛНП в сыворотке крови является доказанным фактором риска развития сердечно-сосудистых заболеваний, обусловленных атеросклеротическим процессом, и их последующего прогрессирования [36]. Снижение уровня ХС ЛНП ассоциируется с улучшением прогноза у пациентов после перенесенного коронарного стентирования, однако даже при достижении целевых уровней ХС ЛНП возможные риски сохраняются.…”
Section: оригинальные статьи §unclassified